Nickel‐based anodes in anion exchange membrane water electrolysis: a review. Issue 7 (3rd May 2022) - Cossar, Emily; Murphy, Frédéric; Baranova, Elena A.
Abstract: BACKGROUND: Anion exchange membrane water electrolysis (AEMWE) is a promising technology for efficiently producing low‐cost hydrogen (H2 ). Of the two half‐cell reactions in AEMWE, the oxygen evolution reaction (OER) is kinetically sluggish, requiring an electrocatalyst to promote the reaction. Nickel (Ni) is a promising non‐noble metal catalyst for OER due to its low cost, high stability, and activity in alkaline media. In an AEMWE, Ni particles form a catalytic layer bound together using an anion exchange ionomer (AEI), which also serves to provide hydroxide ion transport throughout the layer. RESULTS: In this review, reports of lab synthesized Ni particle‐based anode catalytic layers with AEIs, used specifically in AEMWE devices, are summarized from 2015 onwards to highlight the recent research and development of active Ni‐based AEMWE anodes. The synthesis and electrode fabrication method for the anodes is analyzed to offer a perspective on the feasibility of industrial scale AEMWE. As ionomeric binders are an important component of AEMWE anodes, the ionomer type and loading used with the Ni‐based particles is also summarized with a focus on how those parameters affect catalytic performance. CONCLUSION: The literature analysis performed in this work demonstrates the potential of the AEMWE process and provides recommendations for future work on furthering the current understanding of the interactions between the various components of the system. Additionally, it is recommended that future research efforts be focused on further understanding how developed materials perform in a working AEMWE device. © 2022 Society of Chemical Industry (SCI).